Millennials brand awareness - Capelo, Inês Ribeiro dos Santos (2015)
The present work aims at identifying Portuguese Millennials’ characteristics and uses them to create guidelines brands should use when it comes to successfully engaging with this generation in Portugal. A literature review about Millennials and Brand Awareness has been conducted so a research model could be created. The new 3 Cs of Millennials Brand Awareness model identify Content & Creativity, Customer Engagement and Cause-Related Marketing as central pillars brands should considerer when targeting Millennials. Data to test the model was collected through a web-based questionnaire regarding Millennials and Non-Millennial respondents so both generations could be compared. Results show that not all the pillars tested gave the expected results as some of them seem to be more significant and therefore more efficient when connecting to Generation X. Although a lot has been written about Millennials, this study is the first effort on trying to draw a Portuguese reality and test if the existing literature regarding other nationality Millennials can be applied to Portugal. Findings provide useful insights on the Portuguese reality for all firms targeting Millennials and aiming to engage with them. Still, findings should be further verified and lead to new research so stronger guidelines can be identified.